2019
DOI: 10.1038/s41598-019-50193-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered blood-brain barrier models via directed differentiation of human induced pluripotent stem cells

Abstract: Three-dimensional (3D) tissue-engineered models of the blood-brain barrier (BBB) recapitulate in vivo shear stress, cylindrical geometry, and cell-ECM interactions. Here we address four issues associated with BBB models: cell source, barrier function, cryopreservation, and matrix stiffness. We reproduce a directed differentiation of brain microvascular endothelial cells (dhBMECs) from two fluorescently labeled human induced pluripotent stem cell lines (hiPSCs) and demonstrate physiological permeability of Luci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 66 publications
3
72
0
Order By: Relevance
“…Importantly, the protocols mentioned above continue to benchmark differentiated cells using TEER, efflux transporter activity (ETA), and expression of essential BBB junctional proteins (Claudin-5, ZO-1, Occludin, VE-Cadherin), transporters (P-gp, GLUT1), and other factors (PECAM-1, VEGFR2, vWF). Additional recent improvements in the differentiation of iBMECs include the use of fully defined media [20], sorting strategies to increase iBMEC purity [21], and effective methods for the cryopreservation of differentiated cells [22,23], which collectively are improving the reproducibility and scalability of iBMECs for laboratory and potential clinical use.…”
Section: Improvements In Bmec Differentiation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the protocols mentioned above continue to benchmark differentiated cells using TEER, efflux transporter activity (ETA), and expression of essential BBB junctional proteins (Claudin-5, ZO-1, Occludin, VE-Cadherin), transporters (P-gp, GLUT1), and other factors (PECAM-1, VEGFR2, vWF). Additional recent improvements in the differentiation of iBMECs include the use of fully defined media [20], sorting strategies to increase iBMEC purity [21], and effective methods for the cryopreservation of differentiated cells [22,23], which collectively are improving the reproducibility and scalability of iBMECs for laboratory and potential clinical use.…”
Section: Improvements In Bmec Differentiation Methodsmentioning
confidence: 99%
“…Additionally, as new methods to generate iBMECs continue to evolve, the reproducibility of differentiation protocols needs to be considered. iBMEC differentiation efficiency and barrier formation have been shown to vary based on cell line [12], cell seeding density [16], reagent source [84], and response to media components [23,62]. Developing robust protocols that are less sensitive to these variables will undoubtedly improve intra-and interlab reproducibility.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…The human immortalized endothelial cell line hCMEC/D3 [153,154] is widely used for the study of drug transport [163][164][165][166] because it has been thoroughly characterized and it expresses ABC and SLC transporters, as well as tight junctions [167][168][169], despite the fact that the tightness of its monolayer is lower than in intact microvessels due to a lower expression of claudin-5 [169]. Recently, human brain endothelial cells have been obtained from stem cells such as human cord blood-derived stem cells of circulating endothelial progenitor and hematopoietic lineages [156,157], human pluripotent stem cells (hPSCs) [158], and induced pluripotent stem cells (iPSCs) [170,171]. After differentiation and isolation, the hPSC-derived brain endothelial cells monolayers present key BBB characteristics, including tight junctions and functional ABC transporters [158,159,172].…”
Section: In Vitro Models Of the Bbbmentioning
confidence: 99%
“…For example, 3D BBB models commonly utilize nonbrain ECM components including collagen I [27,[54][55][56][57][58] and fibrin [20][21][22]59]. We previously characterized and compared the stiffness of collagen I hydrogels to native mouse brain, and showed that 6 mg mL − 1 collagen is a reasonable proxy for brain stiffness [7]. Additionally, materials with stiffnesses much lower than native brain were not conducive to the formation of stable BBB microvessels [7].…”
Section: Critical Chemical Cues Implicated In Developmental Brain Angmentioning
confidence: 99%
“…To enable imaging of angiogenesis in 3D, we have adapted the fibrin bead angiogenesis assay [6], forming a confluent monolayer of iPSC-derived brain microvascular endothelial cells (dhBMECs) on microbeads (BBB beads). The beads are then embedded in collagen I hydrogels, which mimic the native stiffness of brain parenchyma [7]. We then explore how changes in the chemical and extracellular matrix microenvironment influence in vitro brain angiogenesis.…”
mentioning
confidence: 99%